A Study on the Usage of Cross-Layer Power Control and Forward Error Correction for Embedded Video Transmission over Wireless Links - Fabrizio Granelli; Cristina E. Costa; Aggelos K. Katsaggelos (Advances in Multimedia)
Cross-layering is a design paradigm for overcoming the limitations deriving from the ISO/OSI layering principle, thus improving the performance of communications in specific scenarios, such as wireless multimedia communications. However, most available solutions are based on empirical considerations, and do not provide a theoretical background supporting such approaches. The paper aims at providing an analytical framework for the study of single-hop video delivery over a wireless link, enabling cross-layer interactions for performance optimization using power control and FEC and providing a useful tool to determine the potential gain deriving from the employment of such design paradigm. The analysis is performed using rate-distortion information of an embedded video bitstream jointly with a Lagrangian power minimization approach. Simulation results underline that cross-layering can provide relevant improvement in specific environments and that the proposed approach is able to capitalize on the advantage deriving from its deployment.